KRITERIA TANAH TERLANTAR DALAM PERATURAN PERUNDANGAN INDONESIA - Supriyanto Supriyanto (Jurnal Dinamika Hukum, 2010)
When the State grants the person or legal entity is always accompanied by the obligations set forth in the BAL and the decision letter granting rights. Therefore prohibited from abandoning their land rights holders, and if the rights holders to abandon their land, the BAL has set the legal consequences of the disappearance of the relevant land rights and legal termination and affirmed as the soil directly controlled by the State. Criteria for determining the land has been abandoned, both under Customary Law, Islamic Law, Agrarian Law, Government Regulation No 36, 1998 and also No. 11, 2010 is substantially the same which includes wasteland Object land rights, land rights and management that have a basic mastery land; These lands are not cultivated, not utilized or not utilized in accordance with the circumstances, or the nature and purpose of the rights or basic mastery Therefore land should be maintained. To determine whether a field or farm land has been declared abandoned, the only criterion according to customary law used a specific period.Keywords: Wasteland, State, Rights Holders, A Result Of Law, Land Tenure